Scalp metastases in breast cancer - A. N. Mareeva; V. A. Smolyannikova (State Scientific Center of Dermatovenereology and Cosmetology, 2019)
This paper describes a clinical case of scalp metastases in the setting of breast cancer. The data on the prevalence of the disease in Russia and the necessity of its early diagnostics is provided. The clinical picture and trichoscopic signs of neoplastic processes in the scalp are presented: alopecia foci of 1-3 cm in diameter; foci older than 6 months featuring erythematous and atrophic skin; nodes of the colour of healthy skin or with a yellowish tint sized 1 cm in diameter; trichoscopy - in the foci older than 6 months, the vascular structures are represented by point, thick and thin tree-like vessels. In connection with a poor prognosis for survival when skin metastases are detected, the onco-alertness of practitioners in relation to scalp metastases should be increased.Conflict of interest: the authors state that there is no potential conflict of interest requiring disclosure in this article.